Influence of atmospheric plasma-induced graft polymerization of DADMAC into cotton on dyeing with acid dyes. Issue 11 (2nd November 2017) - Helmy, Hany M.; Hauser, Peter; El-Shafei, Ahmed
Abstract: The primary objective of this work was to generate dyes sites in cotton fiber for acid dyes via free radical graft polymerization of diallyldimethylammonium chloride (DADMAC), to confer cationized cotton, and evaluate the dyeability of the cationized cotton toward acid dyes, which is unprecedented. Plasma-induced graft polymerization of DADMAC on cotton, using different plasma conditions, followed by dyeing with different acid dyes was studied. The color yield of dyed cotton was evaluated using K / S . Light fastness, color change, and staining following accelerated washing cycles were carried out to evaluate the effectiveness of cotton cationization. Cross-section dyed cotton was studied using scanning electron microscopy and showed deep dyeing of acid dyes into cotton fibers. This approach resulted in significant dye uptake into the fibers and considerably reduced the need for effluent treatment.